2004
DOI: 10.1523/jneurosci.3422-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Release in Response to a Psychological Stress in Humans and Its Relationship to Early Life Maternal Care: A Positron Emission Tomography Study Using [11C]Raclopride

Abstract: Mesolimbic dopamine is thought to play a role in the processing of rewards. However, animal studies also demonstrate dopamine release in response to aversive stressful stimuli. Also, in animal studies, disruptions of the mother-infant relationship have been shown to have long-lasting effects on the mesolimbic dopamine system and the hypothalamic-pituitary adrenal axis. We therefore investigated dopamine release in response to stress in human subjects, considering the relationship to early life parental care. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
496
4
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 641 publications
(545 citation statements)
references
References 53 publications
29
496
4
5
Order By: Relevance
“…(2009) suggested that CC homozygosity is associated with higher dopamine availability in striatum and it has further been shown that psychosocial stress increases striatal dopamine levels in individuals reporting low early life parental care (Pruessner, Champagne, Meaney, & Dagher, 2004). As CC homozygotes have higher levels of dopamine available in the striatum, it may be hypothesized that stress‐induced increase in dopamine function is particularly detrimental to CC homozygotes, possibly leading to a hyperdopaminergic state in the subcortical areas.…”
Section: Discussionmentioning
confidence: 99%
“…(2009) suggested that CC homozygosity is associated with higher dopamine availability in striatum and it has further been shown that psychosocial stress increases striatal dopamine levels in individuals reporting low early life parental care (Pruessner, Champagne, Meaney, & Dagher, 2004). As CC homozygotes have higher levels of dopamine available in the striatum, it may be hypothesized that stress‐induced increase in dopamine function is particularly detrimental to CC homozygotes, possibly leading to a hyperdopaminergic state in the subcortical areas.…”
Section: Discussionmentioning
confidence: 99%
“…A similar D 1 /D 2 dichotomy regulates cocaine seeking in non-human primates (Khroyan et al, 2000), and also may suppress and stimulate craving responses in humans, respectively (Haney et al, 1998(Haney et al, , 1999. Together, these studies suggest that D 2 receptors could play a major role in eliciting relapse to cocaine seeking when environmental stimuli such as cocaine-related cues or stress activate the mesolimbic dopamine system (Phillips et al, 2003;Pruessner et al, 2004), while D 1 receptor tone may provide inhibitory regulation over cocaine seeking. In contrast to agonists, both D 1 and D 2 receptor antagonists block reinstatement of cocaine seeking in rats (Weissenborn et al, 1996;Ciccocioppo et al, 2001;Norman et al, 2002;Vorel et al, 2002;Schenk and Gittings, 2003;Gilbert et al, 2005), and indiscriminately block the reinstating effects of nucleus accumbens agonist administration (Bachtell et al, 2005), consistent with well-characterized enabling and synergistic interactions between D 1 and D 2 receptors on behavioral responses (Waddington and Daly, 1993).…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, the emergence of these features from early to late withdrawal parallels time-dependent increases in cocaineseeking behaviors that have been shown to persist from weeks to months following chronic cocaine self-administration (Tran-Nguyen et al, 1998;Grimm et al, 2001). The further intensification of increased D 2 receptor function is particularly troublesome, since it could exacerbate the behavioral response to conditioned stimuli (cues) and stressful situations that activate dopamine release in rats and humans (Rouge-Pont et al, 1998;Phillips et al, 2003;Pruessner et al, 2004), and, thus, facilitate relapse to cocaine use despite efforts to abstain. While our results suggest that reduced D 1 receptor function could exacerbate this situation, they also suggest that restoring the balance between functional D 1 and D 2 receptor responses, whether through increasing D 1 , decreasing D 2 , or both should be considered as a potential therapeutic approach for reversing alterations associated with cocaine addiction.…”
Section: Brain Cocaine Levelsmentioning
confidence: 98%
“…Stressful stimuli lead to dopamine (DA) release in the brains of animals (Abercrombie et al, 1989;Rouge-Pont et al, 1993) and humans (Adler et al, 2000;Pruessner et al, 2004). Considerable evidence links psychotic states and a hyperdopaminergic response to physiological or psychological stressors (Moore et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…These scales have a low intercorrelation, suggesting the two groups represent divergent aspects of vulnerability to psychosis (Chapman et al, 1980). We performed [ 11 C]raclopride positron emission tomography (PET) while exposing subjects to a psychological stressor previously shown to induce significant striatal DA release in healthy volunteers with poor maternal care (Pruessner et al, 2004). Because of these previous findings, we also assessed maternal care using the Parental Bonding Inventory (Parker et al, 1979).…”
Section: Introductionmentioning
confidence: 99%